How biopsychosocial depressive risk shapes behavioral and neural responses to social evaluation in adolescence. Issue 5 (4th March 2021) - Stretton, Jason; Walsh, Nicholas D; Mobbs, Dean; Schweizer, Susanne; van Harmelen, Anne‐Laura; Lombardo, Michael; Goodyer, Ian; Dalgleish, Tim
Abstract: Introduction: Understanding the emotional responsivity style and neurocognitive profiles of depression‐related processes in at‐risk youth may be helpful in revealing those most likely to develop affective disorders. However, the multiplicity of biopsychosocial risk factors makes it difficult to disentangle unique and combined effects at a neurobiological level. Methods: In a population‐derived sample of 56 older adolescents (aged 17–20), we adopted partial least squares regression and correlation models to explore the relationships between multivariate biopsychosocial risks for later depression, emotional response style, and fMRI activity, to rejecting and inclusive social feedback. Results: Behaviorally, higher depressive risk was associated with both reduced negative affect following negative social feedback and reduced positive affect following positive social feedback. In response to both cues of rejection and inclusion, we observed a general neural pattern of increased cingulate, temporal, and striatal activity in the brain. Secondly, in response to rejection only, we observed a pattern of activity in ostensibly executive control‐ and emotion regulation‐related brain regions encompassing fronto‐parietal brain networks including the angular gyrus. Conclusion: The results suggest that risk for depression is associated with a pervasive emotional insensitivity in the face of positive and negative social feedback. Abstract : To understand the emotional responsivity style and neurocognitive profiles of depression‐related processes in at‐risk youth may be helpful in predicting those most likely to develop affective disorders. We explored the relationships between multivariate biopsychosocial risks for later depression, emotional response style and fMRI activity, to rejecting and inclusive social feedback. Data indicate risk for depression in adolescence is associated with a pervasive emotional insensitivity in the face of positive and negative social feedback.